Clinical Manifestations of Pulmonary Tuberculosis in Childhood - Meepolprapai, Meedee; Tantracheewathorn , Taweewong (Vajira Medical Journal : Journal of Urban Medicine, 2022)
Objective: To determine clinical presentations related to pulmonary tuberculosis in children. Methods: A retrospective descriptive study was conducted in children less than 15 years old who were diagnosed with pulmonary tuberculosis at the Department of Pediatrics, Faculty of Medicine Vajira Hospital between January 1st, 2009 - January 1st, 2021. The quantitative data were analyzed into mean and standard deviation and compared between groups by unpaired t-test. The qualitative data were reported by percentage and compares between groups by Chi-square test. Results: A total of 96 patients were included. The average age was 10.3 ± 4.6 years (6 months to 15 years old); 36.5% of patients were male and 63.5% were female, while 84.4% of the patients presented with 2 or more clinical features. Signs and symptoms described in the Thai CPG for Tuberculosis in Children 2019 that were found in this study were cough ≥ 2 weeks (58.3%), fever ≥ 7 days (57.3%), anorexia (42.7%), weight loss (25.0%), inactivity (8.3%), and poor weight gain (1%). Signs and symptoms not included in the Thai CPG for Tuberculosis in Children 2019 were afebrile (34.4%), cough < 2 weeks (28.1%), fatigue (28.1%), hemoptysis (19.8%), night sweat (15.6%), no cough (13.5%), dyspnea (12.5%), chest pain (9.4%), tachypnea (9.4%), fever < 7 days (8.3%), lymphadenopathy (8.3%), chronic vomiting and diarrhea (1%), and asymptomatic (2.1%). Ninety-two patients (95.8%) always had at least 1 clinical feature that was described in the Thai Tuberculosis CPG 2019. However, 4 patients (4.2%) in this study only presented with clinical features not included in the Thai Tuberculosis CPG 2019, including 1 patient who presented with only chest pain, 1 patient who presented with only hemoptysis, and 2 asymptomatic patients. Conclusion: Most of the pediatric patients with pulmonary tuberculosis presented with 2 or more clinical features and almost always had at least 1 symptom that was described in the Thai Tuberculosis CPG 2019.